The pharmacy study program in Guadalajara: 1839-1919 (2023)
Objective: In this article we present an approach to the history of pharmacy education in Guadalajara, a study that covers from 1839, year in which this program was created, until 1919, year in which it was closed at the Escuela Comercial e Industrial para Señoritas. It shows how pharmacy education took shape, its relationship with medicine, the impact of political instability on its evolution, the incidence of pharmacists' work experiences and the emergence of new educational modalities.   Originality: This overview is not limited to the chronological exposition of the circumstances that framed the pharmacy studies. Its exposition is an important empirical basis but it is insufficient to explain to the readers how and why the knowledge, skills and abilities that make up this discipline were modified. In this regard, we believe that the annexation of new knowledge and its ordering have both external and internal motivations.   Method: This is a work of research and a critical analysis of a discipline that was gradually configured until it became a disciplinary corpus. The documentary work is based on historical, educational and institutional funds of the 19th century in Guadalajara. The content we offer here comes from the bibliographic review of studies on higher education in Jalisco as well as from the information compiled from documentary collections of the Archivo Histórico de la Universidad de Guadalajara, The Archivo Histórico de Jalisco, and the Biblioteca pública del Estado de Jalisco.   Strategies/ Data Collection: we approach the teaching contents that make up the curricular basis of the discipline, the educational modalities of pharmacy and the work experiences of pharmacy teachers, for which we resorted to school and curricular documentary materials, to a bibliography guiding the prevailing problems, as well as to the professional and daily life of the actors: employees of the field, proto-pharmacists, newspaper material, history of the curriculum, etc., whose existence is reflected in the documentary and bibliographic record consulted.     Conclusions: In this paper we have tried to show that pharmacy, as a fundamental body of knowledge and therapeutic practices, was a Cinderella during much of its history, because being a fundamental factor in the construction of health in the nineteenth century in Guadalajara, its recognition and status was unjustly denied, even when its medical implementation, contributed greatly to the practice of medicine in terms of minor and gradually major ailments.